Persepsi Siswa terhadap Pemanfaatan Simulasi Virtual PhET dalam Pembelajaran Kimia di SMA Muhammadiyah Sampit - Fakhriyana, Anisa Rahmi; Fatimah Azzahra, Nur; Yayuk, Erna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Limited chemistry laboratory facilities and infrastructure in schools result in suboptimal implementation of practicums. This condition makes it difficult for students to understand abstract chemical concepts due to a lack of direct experimental experience. This study aims to describe students' perceptions of the use of PhET virtual simulations in chemistry learning at SMA Muhammadiyah Sampit and to identify the advantages and limitations of its use as an alternative to practicums. This study used a descriptive qualitative approach. Data collection techniques included observation, interviews, and questionnaires. The research subjects were students at SMA Muhammadiyah Sampit who had used PhET simulations. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the majority of students had a positive perception of the use of PhET simulations because they helped visualize abstract chemical concepts, increased learning motivation, and provided a safe and flexible practicum experience. Obstacles encountered included limited device access, unstable internet connections, and the need for teacher guidance in using the simulations.